'Switch' catalysis: from monomer mixtures to sequence-controlled block copolymers. (13th January 2018) - Stößer, T.; Chen, T. T. D.; Zhu, Y.; Williams, C. K.
Abstract : A 'Switch' catalysis method is reviewed whereby a single catalyst is switched between ring-opening polymerization and ring-opening copolymerization cycles. It allows the efficient synthesis of block copolymers from mixtures of lactones, epoxides, anhydrides and carbon dioxide. In order to use and further develop such 'Switch' catalysis, it is important to understand how to monitor the catalysis and characterize the product block copolymers. Here, a step-by-step guide to both the catalysis and the identification of block copolymers is presented. This article is part of a discussion meeting issue 'Providing sustainable catalytic solutions for a rapidly changing world'.